Basic of Fault Tree (FT) method - Jasrin, Nurin Saqinah; Othman, Siti Amira; Nor Azman, Nor Farah Amirah; Abu Bakar, Nurul Fathihah (Penerbit UTHM, 2021)
A fault tree described the logical relationship between events and causes. This method shows significant success in analyzing the root cause of an accident. This paper will review the basics of the Fault Tree (FT) method including the structure, factors that contribute and FT application.